Unjuk Kerja Mesin Diesel Berbahan Bakar Campuran Biodiesel Jatropha- Jelantah 1:9 - Wahyudi, Wahyudi; Nadjib, Muhammad; Aji, Yogi Purnomo (TURBO [Tulisan Riset Berbasis Online], 2023)
In the context of a rapidly growing industry and increasing energy needs, the dwindling sources of fossil fuels prompt the necessity for alternative fuels. This study focuses on the performance of diesel engines running on a blended biodiesel made from jatropha oil and waste cooking oil in a 1:9 ratio. The aim of this study is to investigate the effects of biodiesel fuel made from jatropha oil and waste cooking oil on diesel engine performance and fuel physical properties. The tests include an evaluation of the fuels physical properties, injection characteristics, engine speed, generated power, and specific fuel consumption (SFC). Results indicate that although this blended biodiesel has higher density and viscosity compared to diesel, it offers promising calorific value and spray angle. Moreover, engines using this fuel showed relatively stable engine speeds and power outputs, along with efficient SFC at higher loads. The jatropha-waste cooking oil biodiesel blend shows potential as a sustainable and environmentally-friendly alternative fuel